The performance of two varieties of water melon citrullus lanatus (thub) matsura and nakai, grafted over pumpkin lagenaria siceraria, zapallo cucurbita moschata, ahuyama cucurbita maxima and estropajo luffa cylindrica graftholders (1992)
In the first semester of 1987 was done this experiment at Universidad Nacional, Palmira. The objectives were to evaluate grafts viability, to quantify production and to give alternatives to phytosanitary problems. It was done a prick or escutcheon graft with water melon small plants from Charleston Gray and Sugar Baby. The summit bud was eliminated and it was longitudinally cut 1.0 - 1.5 cm for inserting the prick cotyledon leaves and the summit bud. Experimental units were distributed in random complete blocks, where experiment treatments were grafted plants and control the varieties sown directly by seeds. The success of the graft system in the described patterns was 90%. The Lagenaria and Cucurbita graftholders produced greater amount of foliate area than Luffa which reduced it greatly. Graftholders did not reduce the organoleptic characteristics of the fruits from the two varieties. - Pests infection in fruits of plants over Cucurbita and Luffa graftholders were reduced.